KENDALA DAN UPAYA PETANI DALAM MENINGKATKAN PRODUKTIVITAS KARET DI DESA SARI MULYA KECAMATAN RIMBO ILIR KABUPATEN TEBO PROVINSI JAMBI - Na’im, Siti Masrifatun; Rianto, Slamet; Zahara, Leni (Pendidikan Geografi, 2013)
The rubber plantation in the village of Mulya Sari is basic agricultural sector for the surrounding of community, where most of the inhabitants work as rubber farmers, either as tenant laborers, plantation owners, or tenants as well as owners of rubber plantations, but it is also as an activity that has been carried down from generation to generation. This study aims to gain an overview of the constraints and efforts to increase the productivity of rubber farmers in view of : 1) land preparation, 2) breeding, 3) planting, 4) treatment, 5) intercepts, 6) marketing. The research is qualitative, the subject of this study through snowball sampling, data were collected through : 1 ) interviews, 2 ) observations, 3 ) documentation. Informants in this study were Mulya Sari villagers work as farmers rubber and rubber plantations have as many as 22 people. Testing the validity of the data in the study used data analysis techniques, data validity, and triangulation. Based on the analysis of data and discussion of matters concluded as follows : 1) the farmers in preparing the land constraint is the cost, effort was good but the farmers still use simple tools, 2) the problems that encountered by farmers get seeds is the cost, distance, and doubts or fraud, the efforts made by farmers themselves by finding and buying from local estate agencies, 3) The constraints encountered in planting farmers are pests, farmers applied effort started from making holes in tillage after planting was carried out, 4) The constraints farmers encountered in the treatment of pests and fungus is the root , the efforts of farmers ranging from cleaning , fertilization , and trimming, 5 ) obstacles encountered farmers are tapping season, farmers efforts for maximum results must be balanced with care, caution in tap, tapping is done 1 week 4-5 times, tapping between the hours of 5:00 to 10:00 am, 6) The constraints encountered farmers in marketing is the distance, cost, and time to wait, the efforts of farmers in marketing is through intermediaries and can only to middlemen and to unit rubber gatherers (upk).